1990
DOI: 10.1128/jb.172.12.7145-7150.1990
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of acetyl coenzyme A by carbon monoxide dehydrogenase complex from acetate-grown Methanosarcina thermophila

Abstract: The carbon monoxide dehydrogenase (CODH) complex from Methanosarcina thermophika catalyzed the synthesis of acetyl coenzyme A (acetyl-CoA) from CH3I, CO, and coenzyme A (CoA) at a rate of 65 nmol/min/mg at 550C. The reaction ended after 5 min with the synthesis of 52 nmol of acetyl-CoA per nmol of CODH complex. The optimum temperature for acetyl-CoA synthesis in the assay was between $5 and 600C; the rate of synthesis at 550C was not significantly different between pHs 5.5 and 8.0. The rate of acetyl-CoA synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…The first biochemical evidence supporting this proposed function was obtained when it was demonstrated that the purified complex synthesizes acetyl-coA (Abbanat and Ferry, 1990). In addition to supporting the proposed function of the complex and further characterization, the results suggested different sites on the enzyme complex for acetyl-coA synthesis and CO oxidation which we further documented in our more recent studies (Lu et al, 1994).…”
Section: Comparison Of the Aminosupporting
confidence: 80%
“…The first biochemical evidence supporting this proposed function was obtained when it was demonstrated that the purified complex synthesizes acetyl-coA (Abbanat and Ferry, 1990). In addition to supporting the proposed function of the complex and further characterization, the results suggested different sites on the enzyme complex for acetyl-coA synthesis and CO oxidation which we further documented in our more recent studies (Lu et al, 1994).…”
Section: Comparison Of the Aminosupporting
confidence: 80%
“…Acetate kinase (3) and phosphotransacetylase (23) catalyze the activation of acetate to acetyl coenzyme A followed by decar- bonylation thought to be catalyzed by the nickel/iron-sulfur component of the CODH enzyme complex (1). The carbonyl group binds to the nickel/iron-sulfur component, and the methyl group is transferred to the corrinoid/iron-sulfur component of the CODH enzyme complex (1). The methyl acceptor for the corrinoid/iron-sulfur component is unknown; however, tetrahydromethanopterin has been shown to be an intermediate methyl carrier in M. barkeri (12).…”
Section: Methodsmentioning
confidence: 99%
“…The estimated native molecular weight of the enzyme was between 132,000 (standard deviation [SD], 1,200) and 141,000 (SD,1,200). Denaturing polyacrylamide gel electrophoresis revealed three protein bands corresponding to molecular weights of 69,000 (SD,1,200),42,000 (SD,1,200), and 33,000 (SD,1,200) and indicated a subunit configuration of alp'lyl. As isolated, the enzyme was inactive but could be reductively reactivated with titanium (III) citrate or reduced ferredoxin.…”
mentioning
confidence: 99%
“…The electron paramagnetic resonance signal is perturbed upon addition of acetyl-CoA, supporting the suggestion that acetyl-CoA is a physiological substrate for the enzyme (16). The synthesis of acetyl-CoA from CH3I, CO, and HSCoA has been reported for CODH from both C. thermoaceticum (6) and M. thermophila (1). However, the cleavage of acetyl-CoA has not been demonstrated with any purified methanogenic CO dehydrogenase.…”
mentioning
confidence: 99%